Utilising competitive intelligence, a key component of knowledge management, to formulate a strategy to develop and manage international markets - Marsal, Jose Javier (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2006.